Vocal difficulties perceived by patients with Parkinson’s disease and their families. A comparative study - Jara Cabrera, Gerson; Hernández Osses, Martín (Revista de Investigación en Logopedia, 2025)
People with Parkinson’s disease (PD) face voice-related difficulties. However, it is suggested that they may have a deficit in the perception of their own vocal problems. The objective of this study was to evaluate the perception of vocal difficulties in individuals with PD and compare it with the perspective of their relatives. A non-probability convenience sample was used, resulting in a final sample of 72 participants, composed of 36 patients with PD and 36 relatives. The Vocal Handicap Index (VHI-30) was used to assess vocal disability in patients with PD, while an adaptation of the same instrument was used for relatives. One-way ANOVA was applied to examine differences in the measures between the two groups. Among the results, 73.6% of patients with PD perceived a mild vocal disability. The mean score estimated by relatives was higher than that of patients with PD, both in the total test and in its subscales (functional, physical, and emotional). When analyzing the results by stage of disease progression, it was observed that perceived vocal difficulties increase as the disease progresses, especially among family members. Patients with PD perceive vocal difficulties more intensely, especially in functional aspects, indicating that patients tend to become more introverted. Patients with PD, on the other hand, primarily perceive physical difficulties, such as tension and strain when speaking.